FEEDING OF ULVA LACTUCA EXTRACT AGAINST THE IMMUNE PARAMETERS AND SURVIVAL OF DUCK GROUPER FISH (Cromileptes altivelis) - Metungun, Jakomina; Beruatjaan, Mariana; Hatijahubessy , Hendro; Putnarubun, Cenny (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2025)
High mortality in humpback grouper infected with Vibrio alginolitycus disease is a major problem in farming activities. The aim of this research was to examine the effect of oral administration of Ulva lactuca extract in feed to improve the non-specific immune system and survival of Vibrio alginolitycus. This research was carried out from July to December 2023 at the Tual State Fisheries Polytechnic Campus. The method used was a Completely Randomized Design (CRD) method with 3 treatments, namely treatment A Ulva extract 1 gr/kg feed, treatment B 2 gr/kg feed and treatment C 3 gr/kg feed, plus 2 treatments as controls, namely K( +) was not fed Ulva extract, was challenged with Vibrio alginolyticus bacteria 108 CFU/ml and K (-) was not fed Ulva extract, was not challenged but was injected with PBS. The results of the study showed that oral administration of Ulva lactuca extract containing antibacterial compounds was thought to be able to increase the non-specific body defense system of humpback grouper, characterized by increased levels of hemoglobin (Hb), total erythrocytes, total lymphocytes found in treatment C at a dose of 3 g/kg feed. and the best survival in treatments B and C was 80%.